Policy For Fulfilling Teacher Needs In The Pringsewu - Lampung Regency Area - Ulfatul Khoiriyah; Suryadi Suryadi; Siti Rochanah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Data from the Ministry of Education, Culture, Research and Technology (Kemdikbudristek) shows that Indonesia needs 1.3 million teachers by 2024. In an effort to meet the needs of teachers, the recruitment of government employees with work agreements (PPPK) for functional positions is organized with a strict selection system. PPPK procurement in each region must submit a formation proposal to the Ministry of Education, Culture and Research by first analyzing teacher needs. This applies to Pringsewu district, Lampung province. Based on the regulation of the Minister of National Education no. 7 of 2010 states that in fulfilling teacher needs, teacher needs analysis is carried out by considering 1) the ratio of teachers and students, 2) the distribution of teachers, and 3) the projection of fulfilling the teacher workload of at least 24 face-to-face hours in 1 week. The research subjects were; Head of the Primary School Teachers and Education Personnel (GTK) Section of the Pringsewu District Education and Culture Office. The research was conducted using descriptive-qualitative methods. The results that the regional government policy of Pringsewu Regency seeks to provide for teacher needs by proposing the formation of teacher needs to the Kemendikbudristek based on the number of PPPK formations in 2023 will be 668 formations (teachers). The proposed formation is made in accordance with the results of the GTK section head's analysis so that it can balance the supply and demand of teachers needed in Pringsewu district.